Explaining civilian control of militarisation in Indonesia: The case of military law amendment - Batara Gunawan, Aditya (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
This study explores the civilian control of militarisation practice in Indonesia, which refers to the discursive politics involving citizenry in the legitimisation mechanism of the use of military force for defence and non-defence objectives. To explore the empirical manifestation of the concept, the study applies the discourse network analysis method, which combines qualitative content analysis and social network analysis to investigate the public debates over the military law amendment. Accordingly, the study collected a dataset of 227 statements from 55 actors in 118 news articles on the military law amendment from May to July 2023. The analysis reveals that, first, the discourse was dominated by actors from non-governmental organisations, think tanks, and academia. Second, the discourse was driven by several main concerns, such as the return of military dual-function doctrine, the current state of military personnel occupying civilian posts, and the urgency of public participation in the deliberation process of the amendment. This article argues that the configuration of the dominant actors and the prominent issues reflect the prevalence of inward-looking defence policy orientation issue in Indonesia.